Burqa de chair - Arcan, Nelly; Huston, Nancy (Seuil, 2011)
« Septembre 2001-septembre 2009 : en l'espace de huit ans, une jeune femme déploie son chant et disparaît. Huit ans seulement pour entrer avec fracas dans la littérature et pour s'échapper du monde tout aussi violemment. Nelly Arcan était une guerrière, sous les fragiles apparences d'un ange blond. Son courage intellectuel n'avait d'égal que son effroi de vivre, c'est-à-dire d'habiter un corps. Un corps de femme, exposé et convoité, prison et camisole, étendard et linceul. Burqa de chair, disait-elle dans une formule saisissante. Il semblerait que très tôt elle ait appris à poser les bonnes questions, celles qui dérangent, que s'emploie à détailler Nancy Huston dans sa préface. Les textes qu'on lira ici sont du meilleur Nelly Arcan. Dernières pierres blanches au bord d'une route interrompue, ils nous donnent l'occasion d'entendre encore une fois la beauté de cette langue inimitable, étourdissante, et qui laisse le lecteur hors d'haleine. »–Quatrième de couverture.
La nouvelle La honte a été donné en lecture au cours LIT3495.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; arts; canada; corps; cours; discipline; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

N'est pas mère qui veut. Le paradoxe de l'adoption internationale - Reysoo, Fenneke; Bos, Pien (Nouvelles Questions Féministes, 2011)
La circulation d’enfants entre une mère biologique et des parents adoptifs soulève des questions sur la pluralité des systèmes de genre et les inégalités sociales méconnues jusqu’ici. Nous menons une réflexion sur la situation paradoxale qui lie deux systèmes de genre : en Inde, il enjoint des femmes non mariées à renoncer à vivre leur maternité et, en Occident, il pousse les femmes avec un emploi à retarder la conception de leur premier enfant, ce qui augmente le risque de fécondabilité réduite et ouvre la voie au recours à l’adoption. Notre étude, au Tamil Nadu (Inde), parmi les mères biologiques montre que la production d’enfants adoptables relève de rapports de pouvoir très complexes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; corps; cours; discipline; inde; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Miss representation (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Place: San Francisco, Calif.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis